'Communicative Equations': Towards a More Agile PR Practice in the Network Society. Issue 4 (November 2015) - Duarte, João
Abstract : Agile PR therefore explores the benefits of a coordinated teamwork, consistently focused on deliverables and always ensuring relevant information is shared at all times, driving better and more informed decision making, and more resilient research, planning, execution and evaluation of PR work.